‘The Subversion of Dialects’: Changing Attitudes towards Rural Varieties of Galician - Montserrat Recalde; Mauro Fernández (Languages, 2024)
The gheada and the seseo are the two pronunciations most stigmatised by the top-down standardising tradition of Galician from the mid-19th century. Social stereotypes of peasantry, ignorance, and vulgarity were built on them. Nowadays, those stereotypes are the basis for indexical pointing. These pronunciations were outlawed from schools in the past. Today, despite having been considered standard by The Royal Galician Academy since 1982, they are almost absent from the classrooms, including those of Galician language and literature. This situation is detrimental to the linguistic capital of its users as compared to that of standard speakers. Nonetheless, since the end of the 20th century, there has been a social resignification of the gheada and seseo, symbolically used to express authenticity, ethnolinguistic adherence, and/or socio-political and cultural resistance. Currently, the emergence of vernacular language ideologies (VLIs) counterbalances the weight of standard language ideologies (SLIs) on these phenomena. This article analyses the linguistic attitudes of a sample of young people towards these two dialectal varieties as opposed to the standard pronunciations. It also identifies the indexical associations of contrasting varieties and their evolution over time. For this purpose, the matched-guise technique in combination with semantic differential scales (SDSs) has been applied. The results show that whereas standard pronunciations index social success, dialectal pronunciations index solidarity. However, while the standard indexical values are very stable, a rise in dialectal ratings is observed over fifteen years, which means an improvement of the attitudes towards them. As in other European minority languages, this phenomenon indicates a process of value levelling of the linguistic varieties and the growing weight of the VLIs in late modernity in Galicia.